The Influence of Video-Based Health Education on Burn First Aid: Family Knowledge and Actions - Yuni Syafitri; T. Abdur Rasyid; Dian Roza Adila (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Burn injuries continue to be a global health issue. Incidents of burns often occur within households, where improper management can lead to increased mortality and disability rates. Therefore, health education related to burn management is crucial. The aim of this study was to investigate the impact of health education using videos on the knowledge and actions of families in providing first aid for burn injuries. This quantitative study employed a pre-experimental design with a one-group pre-test and post-test approach. The population consisted of families with a history of burn injuries within their households. The sample comprised 20 respondents selected through consecutive sampling technique. Data were collected using a knowledge questionnaire and an observation sheet for assessing burn first aid, which underwent validity and reliability testing. Univariate and bivariate analyses were conducted using the Wilcoxon test. The research findings revealed that the majority of respondents were aged 18-35 years (55%), with the most common occupation being housewives (55%), and the majority had a high school education (50%). The median pre-test knowledge score was 8, while the post-test knowledge score was 17. The median pre-test burn first aid action score was 3, while the post-test score was 8.5. The Wilcoxon test results for knowledge and burn first aid actions before and after health education using videos yielded a p-value of 0.000. In conclusion, health education using videos has a significant impact on the knowledge and actions of families in providing first aid for burn injuries. The researchers recommend that families acquire the proper skills for managing burn injuries to prevent complications.